Accomplishing authentic writing tasks: Ventures into academic publication by Ecuadorian EFL teachers - Orosz, Agnes; Carrasco, Marcela; Jaramillo, Daniela; Békés, Erzsébet (Indonesian Journal of Applied Linguistics, 2019)
Academic writing and subsequent publishing have become an important part of the career advancement and professional development of those engaged in English language teaching worldwide. The aim of this study was to explore a solution to the gap in the academic writing skills of Ecuadorian English teachers in tertiary education. Our survey of 65 Ecuadorian English teachers showed that 92% of teachers had never published. Their reasons for not having done so included lack of self-confidence that they could produce publishable material, lack of English proficiency, lack of academic writing skills and lack of time. The intervention described in the research study involved engaging nine English teachers of an academic writing training course in authentic tasks that required writing academically for five carefully chosen ELT publications. An attainable goal was set: the participants of the training course held in November-December 2016 were invited to write book reviews and short articles on the intervention itself. Till the end of April 2018, altogether seven academic-level texts (four book reviews, one webinar review, one short article, and a concise book) were published. Two of the course participants decided early on that they did not want to participate in the optional academic writing and publishing activity, and a further four did not follow up on their initial steps; nonetheless, as a result of the intervention and its follow-up phase, five of the nine participants (including two that initially abstained) eventually published academic-level texts in recognized ELT publications. The results of the study suggest that tertiary level (non-native) English teachers can start writing academically and achieve success in the competitive world of publishing if realistic tasks are set, the trainees are mentored systematically, and the time frame (18 months) allows the submission, revision, and editing of academic articles to develop organically, leading to polished products.